Pengaruh Citra Merek Terhadap Minat Beli Ulang yang Dimediasi oleh Kepuasan Pelanggan Hand and Body Lotion Nivea di Kota Bandung - Vita Try Azzely; Vita Dhameria (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2025)
This study aims to examine how brand image influences repurchase intention, with customer satisfaction serving as a mediating variable among consumers of Nivea hand and body lotion in Bandung. Using a quantitative approach involving 60 respondents, data were collected through questionnaires and analyzed using multiple regression and Sobel tests with the assistance of SPSS version 27. The results indicate that brand image has a positive effect on both customer satisfaction and repurchase intention, with customer satisfaction proven to be a significant mediating variable. These findings provide theoretical contributions and practical implications for enhancing customers’ repurchase intention toward the brand